In-house semi-nested reverse transcription polymerase chain reaction for the detection of HCV-RNA in serum with low viral load - Hamzah, Hairul Aini; Mustafa Mahmoud, Mohammed Imad Al-Deen; Abdullah, Nasuruddin (2013)
Hepatitis C is a viral disease caused by hepatitis C virus. Patients infected with the virus may develop chronic hepatitis, who were remain asymptomatic. Our objective is to established a sensitive and reliable assay for the detection of HCV-RNA in serum. Sera were collected from 39 chronic HCV patients and 53 from patients with negative anti-HCV. Viral RNA was extrcated and subjected for RT-PCR or semi-nested RT-PCR. Results showed high sensitivity of the assay which can detect up to 2.15 IU/ml of viral load. The specificity of the assay was also evaluated. Thus, the extablished protocol was reliable for the detection of HCV-RNA from serum.